Decreased neurotensin levels as a biomarker in resistant hypertension. (2nd April 2020) - Bolat, Ismail; Pusuroglu, Hamdi; Demir, Ali Rıza; Ornek, Vesile; Erturk, Mehmet
ABSTRACT: Objective : Although neurotensin is found throughout the body including cardiovascular structures, the correlation of plasma neurotensin levels with resistant hypertension (RH) has never been examined. Therefore, we aimed to compare plasma neurotensin concentration, between patients with RH and those with controlled hypertension (CH). Methods : Forty-one patients with RH and 45 patients with CH who had undergone outpatient ambulatory blood pressure measurements were prospectively recruited. RH was defined as uncontrolled blood pressure despite using three antihypertensive agents including a diuretic or need of four or more drugs to control blood pressure. The demographic properties, medications, laboratory parameters including neurotensin levels, and echocardiographic parameters were recorded. Results : There was no significant difference among groups in terms of age, sex, smoking or body mass index. Office and ambulatory blood pressures and mean number of antihypertensive drugs used were significantly higher in patients with RH compared to patients with CH. Plasma neurotensin levels were significantly lower in patients with RH (median: 0.380 ng/ml; interquartile range: 0.292–0.471) than in the patients with controlled blood pressure (median: 0.638 ng/ml; interquartile range: 0.483–0.783). Multivariate and receiver-operating characteristics curve analyses showed that neurotensin is an independent predictor for RH and the optimal cut-off value of neurotensin for RH was lower than 0.509 ng/ml, with a sensitivity of 85.4% and a specificity of 73.3% (area under the curve = 0.793, 95% CI: 0.691–0.894, p < .001) Conclusion : This study is the first to show a correlation between lower neurotensin levels and RH.